0.3-V Voltage-Mode Versatile First-Order Analog Filter Using Multiple-Input DDTAs - Kumngern, Montree; Khateb, Fabian; Kulej, Tomasz; Steffan, Pavel (My University, 2023)
This paper presents a versatile first-order analog filter using differential difference transconductance amplifiers (DDTAs). The DDTA employs the bulk-driven (BD) multiple-input MOS transistors technique (MI-MOST) operating in the subthreshold region. This results in low-voltage and low-power operational capability. Therefore, the DDTA, designed using 130 nm CMOS technology from UMC in the Cadence environment, operates with 0.3 V and consumes 357.4 nW. Unlike previous works, the proposed versatile first-order analog filter provides first-order transfer functions of low-pass, high-pass, and all-pass filters within a single topology. The non-inverting, inverting, and voltage gain of the transfer functions are available for all filters. Furthermore, the proposed structure provides high-input and low-output impedance, which is required for voltage-mode circuits. The pole frequency and voltage gain of the filters can be electronically controlled. The total harmonic distortion of the low-pass filter was calculated as −39.97 dB with an applied sine wave input signal of 50 mVpp@ 50 Hz. The proposed filter has been used to realize a quadrature oscillator to confirm the advantages of the new structure.
Keywords: analog filter; differential difference transconductance amplifier; low-voltage low-power circuit; voltage-mode circuit